Multimodality and the Semiotic Bundle Lens: A Constructive Resonance with the Theory of Objectification - Cristina Sabena (PNA: Revista de Investigación en Didáctica de la Matemática, 2018)
The paper situates mathematics teaching-learning processes within a multimodal perspective and discusses a semiotic approach apt to seize this dimension, namely the Semiotic Bundle lens. This analytical tool considers the great variety of semiotic resources through which mathematical meanings emerge and evolve in the classroom, ranging from embodied ones such as gestures, to symbolic systems. In particular, the analysis considers them in a systemic and dynamic way. The theoretical account is illustrated by means of an example on children spatial conceptualization, carried out in kindergarten. The data analysis will constitute a background against which the connections with the Theory of Objectification will be highlighted, showing a constructive resonance between the two theories.